Reducing the surface recombination during light-driven water oxidation by core-shell BiVO4@Ni:FeOOH. (20th March 2019) - Zhang, Xiaofan; Li, Hao; Kong, Weiqian; Liu, Huili; Fan, Hongbo; Wang, Mingkui
Abstract: The photocurrent of BiVO4 is limited by surface recombination not surface catalysis, which is currently reported as the main restrict factor for high efficiency photo-electrochemical (PEC) water splitting. To solve this problem, an ultrathin Ni:FeOOH (∼8 nm) modified nanoporous BiVO4 photoanode (BiVO4 @Ni:FeOOH) was constructed with core-shell structure for PEC water oxidation. Attributed to the p-n hetero-junction formed between BiVO4 and Ni:FeOOH, the photocurrent density of BiVO4 @Ni:FeOOH increased by a factor of 11 (2.86 mA cm −2 at 1.23 V vs. RHE), together with ∼180 mV negative shift of onset potential under AM 1.5 G irradiation (100 mW cm −2 ) in comparison to the pristine BiVO4 . More importantly, detailed insight into the fate of the photo-generated charge carriers at the surface is investigated. Intensity modulated photocurrent spectroscopy (IMPS) is used to investigate the surface carrier dynamics of BiVO4 and BiVO4 @Ni:FeOOH. IMPS results and hole scavenger measurement (HSM) certify the main role of Ni:FeOOH is to improve surface recombination by largely decreasing the surface recombination rate constant (krec ), not surface catalysis. This work demonstrates Ni:FeOOH can facilitate local surface kinetics and reduce recombination rates as well and be used in other photoelectrodes especially the photoanodes with surface defects for PEC water splitting.